Атрибуція речей із забутого комплексу з розкопок біля с. Васильків - Бабенко, Л.І.; Ліфантій, О.В. (Археологія і давня історія України, 2019)
У статті здійснена спроба атрибуції речей, що походять із розкопок Ю. Ф. Абази біля села Васильків (сучасна Черкаська обл.) у 1895 р. In 1895 Yulia F. Abaza made the archaeological excavations near Vasylkiv village of Zvenyhorod district. The found materials were given to the Archaeological museum of Kiev Saint Vladimir Imperial University that has not survived till nowadays. In 1899 these artefacts were presented as one Scythian burial mound assemblage at the 11th Archaeological Congress exhibition in Kyiv, though the analysis of collection’s items demonstrate their cultural and historical broad range. There are ca. fifteen vessels of Trypillia and one — of Middle Dnieper cultures. The biggest part of the assemblage under discussion is presented by two horizons of Scythian Age. Also one sword belongs to the Sarmatian culture. This diversity makes impossible to assume belonging of all described items to one archaeological complex.